Evaluation of nutrition components in Lanzhou lily bulb by confocal Raman microscopy - Li, Yuee; Wang, Huihui; Zhang, Wenbo; Wu, Haining; Wang, Zhong (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2021)
Lanzhou lily is a famous lily variety in China, which has many advantages different from other lily varieties. It is rich in nutrients and can be used as medicine or food. The present study is performed to evaluate the quality of Lanzhou lily by Raman spectroscopy. Here, Raman spectra of lily bulbs were collected by confocal Raman microscopy. Through study of a variety of samples, we found that Raman peaks of several important nutrients including starch, sucrose and amino acids were clearly observed from scales of lily bulb, while strong characteristic peaks of ferulic acid were observed at the epidermis of the same scale due to the stimulation of the external environment. We also compared lily bulbs with various sizes and shapes using an average Raman spectrum of selected area. Then, changes of nutrients were quantitively analyzed in different storage period. The results show that the nutrient components including starch, sucrose, amino acids and ferulic acid can be evaluated by Raman spectroscopy. Then the quality of Lanzhou lily can be evaluated by Raman spectroscopy. This is valuable for quality evaluation of lily using non-destructive methods. Our study is performed to evaluate the quality of Lanzhou lily by Raman spectroscopy. We found that Raman peaks of several important nutrients including starch, sucrose and amino acids were clearly observed from scales of lily bulb, while strong characteristic peaks of ferulic acid were observed at the epidermis. We also investigated the distribution of starch and protein using confocal Raman imaging, and the results were consistent with previous reports. [Display omitted] •Raman spectroscopy are used to analyze the compositions of Lanzhou lily.•The sample preparation process is simple and nondestructive to biological tissue.•A series of samples with different sizes, storage time and harvest time show significant differences in Raman spectra.•The starch grains are clearly imprinted by Raman imaging, with the birefringence reflected.